Harmonic resonance in electrical grids with photovoltaic distributed generation - Fortes, Rárison R. A.; Oliveira, Luis C. O. [UNESP]; De Souza, Julio B. [UNESP]; Buzo, Ricardo F. [UNESP]; Álvarez, Juan J. Pérez [UNESP] (Institute of Electrical and Electronics Engineers (IEEE), 2016)
In this paper it is presented the analysis of an electric power distribution branch containing a photovoltaic system, considering the generation and propagation of harmonic distortion. The obtained results refer to an operational configuration of the grid with a parallel resonance at a harmonic frequency generated by the photovoltaic system due to an installed capacitor bank. Power Simulator- PSIM is used as a simulation platform to evaluate the propagation of current harmonic distortion as well the associated voltage harmonic distortions. A technique to identify the network resonance frequencies is also proposed. Under these conditions, violations of the voltage total harmonic distortion operational limits are evaluated, as well as the recommended operating limits for the installed capacitor bank.
Keywords: distributed generation; harmonic distortion; parallel resonance; photovoltaic system; power quality